Structural Characterization of Polysaccharides from Noni (Morinda citrifolia L.) Juice and Their Preventive Effect on Oxidative Stress Activity - Bin Zhang; Xiaoyu Wei; Peiwen Du; Huangqun Luo; Lanfang Hu; Liping Guan; Guangying Chen (Molecules)
Polysaccharides are very promising molecules in the field of pharmacotherapy. Knowing this, the aim of this study was to extract, characterize, and evaluate the action of the polysaccharides in noni juice, using biological models of Type 2 diabetes mellitus processes. In this study, one polysaccharide named NJSPd−1 was separated from fermented noni fruit juice. The characterization assay showed that NJSPd−1 had a molecular weight (Mw) of 18,545 Da. NJSPd−1 consisted of galacturonic acid, galactose, rhamnose, and arabinose, with a molar ratio of 28.79:20.34:19.80:18.84 according to HPGPC analysis, and the glycosidic bond mainly included →4)-α-D-GalAp-(1→, 4)-β-D-Glcp-(1→, →2)-α-L-Rhap-(1→, and →3)-α-L-Araf-(1→. The prevention of oxidative stress activities by NJSPd−1 was evaluated using high-glucose-induced oxidative stress in HepG2 cells. In vitro results showed that NJSPd−1 influenced the downregulation of the proteins and genes Nrf2, Keap1, HO-1, and NQO1 in HepG2 cells. These results suggest that NJSPd−1 exerted a protective effect against oxidative stress in HepG2 cells by activating the Nrf2/HO-1/NQO1 signaling pathway.